MANAJAMEN KOMUNIKASI PENDIDIKAN DALAM PERSFEKTIF AL-QUR’AN - Muslimin Hutapea; Suheri Sahputra Rangkuti (STAI Tuanku Tambusai, 2022)
The science development and information technology sophistication in the era of globalization that can be seen from television, internet and other media almost make the world has no boundary between regions and countries so that foreign cultures (from the west) which the majority deviates from the norms and rules of Islam are easily accepted by many countries including Indonesia. This condition causes young generation to experience a moral crisis that needs a serious attention from educators, especially parents in fortifying their children with a strong faith in order not to get carried away into the valley of error through the communication process that is managed effectively. To fortify a child with a strong faith, it is necessary to develop a concept of education derived from the Qur'an which is the first and main source of Islamic teachings. For that reason, a study entitled